Optimization model of noise and vibration in passenger car cabin on pavement road - Ahmad Kadri, Junoh; Zulkifli, Mohd Nopiah; Wan Zuki Azman, Wan Muhamad; Mohammad Hosseini, Fouladi; Mohd Jailani, Mohd Nor; Ahmad Kamal, Ariffin (Universiti Malaysia Perlis (UniMAP), 2010)
1st Regional Conference on Applied and Engineering Mathematics (RCAEM-I) 2010 organized by Universiti Malaysia Perlis (UniMAP) and co-organized by Universiti Sains Malaysia (USM) & Universiti Kebangsaan Malaysia (UKM), 2nd - 3rd June 2010 at Eastern & Oriental Hotel, Penang.